Organized Sports as a Preventative Factor for Substance Abuse: A comparison of ADHD and non-ADHD individuals - Bjarki Jóhannsson 1991- (2018)
Research has shown that individuals with attention deficit-hyperactivity disorder (ADHD) have a greater chance of developing substance use disorders than individuals without ADHD. Substance abuse amongst teenagers in Iceland has been decreasing in the past decade, in part due to the encouragement for adolescents to participate in organized sports. This study investigated whether organized sports had the same preventative effects on lifetime alcohol, smoking and marijuana use between ADHD and non-ADHD individuals. A questionnaire was administered by ISCRA, all the participants were students in 8th, 9th and 10th grade, aged from 13 to 18. There was a total of 11.013 responses with a response ratio of 86.3%. For this study a random sample of 2127 participants was used, gender distribution was even with 1045 boys and 1063 girls, 19 participants did not disclose their gender. Results showed that the effect of organized sports on lifetime alcohol use and smoking was not significantly different for participants with ADHD and without ADHD. However organized sports had more of a protective effect on individuals with ADHD when it came to lifetime marijuana use. Keywords: attention deficit-hyperactivity disorder, organized sports, substance abuse Rannsóknir hafa sýnt að einstaklingar með athyglisbrest og ofvirkni (ADHD) eru líklegri til þess að neyta vímuefna en einstaklingar sem ekki hafa ADHD. Vímuefnanotkun meðal unglinga hefur farið minnkandi á Íslandi undanfarinn áratug, að hluta til vegna aukinnar áherslu á skipulagða íþróttastarfsemi meðal unglinga. Þessi rannsókn skoðaði hvort skipulögð íþróttastarfsemi hafði sömu verndandi áhrif gagnvart lífstíðar áfengis-, reykinga- og maríjúananotkunar meðal einstaklinga með og án ADHD. ISCRA lagði fyrir spurningalista meðal allra nemenda í áttunda, níunda og tíunda bekk. Í heildina fengust 11.013 svör, svarhlutfallið var 86,3%. Fyrir þessa rannsókn var notað slembiúrtak sem innihélt 2127 þátttakendur, kynjahlutfall var jafnt með 1045 stráka og 1063 stelpur, 19 þátttakendur ...